2011
DOI: 10.12693/aphyspola.119.369
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical and Electrical Properties of Plasma Deposited Thin Films from Hexamethyldisilazane Compound

Abstract: Silicon organic thin films have been prepared by RF hollow cathode plasma chemical vapor deposition system, from hexamethyldisilazane (HMDSN) as the source compound, under different plasma conditions, namely feed gas and applied RF power. The feed gas has been changed from argon to nitrogen, and the power has been varied between 100 W and 300 W in N 2 /HMDSN plasma. The structural properties of the deposited films have been investigated by the Fourier transform infrared spectroscopy technique. Spectrophotometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, the AFM measurements showed that the formation of the layer structure for the coating systems on the PDMS substrate is comparable to that on a Si wafer. Saloum et al found that a change in auxiliary gas from nitrogen to argon is associated with a higher fragmentation of the HMDSN precursor as described above [55]. A higher fragmentation of the monomer, on the other hand, may cause nanoparticles to be formed already in the plasma bulk, which are adsorbed on the substrate surface during the coating process.…”
Section: Characterization Of Structural Coating Propertiesmentioning
confidence: 92%
See 2 more Smart Citations
“…However, the AFM measurements showed that the formation of the layer structure for the coating systems on the PDMS substrate is comparable to that on a Si wafer. Saloum et al found that a change in auxiliary gas from nitrogen to argon is associated with a higher fragmentation of the HMDSN precursor as described above [55]. A higher fragmentation of the monomer, on the other hand, may cause nanoparticles to be formed already in the plasma bulk, which are adsorbed on the substrate surface during the coating process.…”
Section: Characterization Of Structural Coating Propertiesmentioning
confidence: 92%
“…Saloum et al were able to demonstrate the same behavior when comparing nitrogen and argon as auxiliary gas: FT-IR measurements showed that in the presence of atomic nitrogen an increase of the N-H band is accompanied by a decrease of the Si-C bond. Reason for this may be the insertion of N-H into the Si-C bonds and in the segments of the film network, whilst N-H was formed in the plasma bulk through chemical reaction between nitrogen and hydrogen released from the precursor [55]. This seems to further favor the incorporation of oxygen during post-oxidation, whereby the mechanisms cannot be fully explained here.…”
Section: Characterization Of Chemical Coating Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…In terms of general applications, thin films have reached various fields of science. In the construction sectors, especially those related to metal materials, thin layers are used as a material to increase corrosion resistance [7]. In the field of electronics, thin films are used to Trends Sci.…”
Section: Introductionmentioning
confidence: 99%